Mediating effects of working memory on the relationship between chronic pain and overgeneral autobiographical memory. Issue 3 (16th March 2021) - Liu, Xianhua; Yang, Hong; Li, Sisi; Wan, Di; Deng, Yu; Fu, Yonghui; Qu, Qiong; Zhong, Linying; Hu, Yiqiu
ABSTRACT: This study is to explore the function of working memory (WM) and autobiographical memory (AM) in patients with chronic pain. Totally, 331 patients with chronic pain and 333 healthy controls were recruited. These subjects were subjected to assessment with Pain Assessment Protocol (PAP), Visual Analogue Scale (VAS), Working Memory Index (WMI) and Autobiographical Memory Test (AMT). Patients with chronic pain scored significantly lower in WMI and higher in overgeneral autobiographical memory (OGM) of AMT. Chronic pain was significantly negatively related with WM and positively related with OGM. The structural equation model indicated that WM mediated the relationship of chronic pain and OGM. These findings suggest that WM and AM are impaired in the patients with chronic pain, , chronic pain is closely related with OGM, and WM acts an important mediating role between chronic pain and OGM.